Exploring the function of stromal cells in cholangiocarcinoma by three-dimensional bioprinting immune microenvironment model - Li, Changcan; Jin, Bao; Sun, Hang; Wang, Yunchao; Zhao, Haitao; Sang, Xinting; Yang, Huayu; Mao, Yilei (Frontiers in Immunology, 2022)
The tumor immune microenvironment significantly affects tumor progression, metastasis, and clinical therapy. Its basic cell components include tumor-associated endothelial cells, fibroblasts, and macrophages, all of which constitute the tumor stroma and microvascular network. However, the functions of tumor stromal cells have not yet been fully elucidated. The three-dimensional (3D) model created by 3D bioprinting is an efficient way to illustrate cellular interactions in vitro. However, 3D bioprinted model has not been used to explore the effects of stromal cells on cholangiocarcinoma cells. In this study, we fabricated 3D bioprinted multicellular models with tumor cells and stromal cells. Compared with cells cultured in two-dimensional (2D) environment, cells in 3D bioprinted models exhibited better proliferation, higher expression of tumor-related genes, and drug resistance. The existence of stromal cells promoted tumor cell activity in 3D models. Our study shows that 3D bioprinting of a multicellular immune microenvironment is an effective way to study the effects of stromal cells on cholangiocarcinoma cells.